Global convergence of tax judgments and principles between South African courts and foreign courts: Assessing evidence of convergence in South African case law and its desirability in a South African context - Dewar, Michael (Department of Finance and Tax, 2019)
This paper seeks to assess the presence of convergence of domestic and foreign tax judgments and principles in South African courtrooms. Besides the practical fact of assessing the general view of South Africa courts to the application of foreign cases and principles, it also explores whether convergence is beneficial to South African in a variety of contexts. The case law review concludes that while South Africa courts are bound only to take foreign cases as persuasive and not as binding, they appear to assign such cases similar weight to domestic cases, refuting them primarily on the facts of the matter as they would any other domestic citation and not dismissing them purely due to their foreign nature. With the evidence clearly favouring the existence of convergence, the paper goes on to assess whether this convergence is a benefit to South Africa, first in the example of the specific case law reviewed and then in the larger context of South Africa as a country. The cases largely show benefits from the inclusion of foreign cases, with the only caution that the court must be sensitive to the context of a foreign case, particularly when dealing with principles of language or business which may be culturally-specific. In the larger context, the paper cites writers from American, European and South African sources. The conclusion from these varying arguments is that convergence is primarily a positive force to a country of South Africa’s relative size, position and economic power. The greatest risk the country faces would be to be forced in a form of convergence which is detrimental to its needs by other more powerful countries – however, historic evidence of how convergence in the European Union has led to clusters of countries with similar principles (and with free movement between these groups) suggests that it is far from likely that convergence will become such an autocratic influence.